Quality culture in postgraduate education: student’s satisfaction perspectives - Tu, Nguyen Thanh; Huong, Tran Thi Thu; Nham, Nguyen Thi; Tuan, Nguyen Anh (Edelweiss Applied Science and Technology, 2024)
Although there is growing interest in quality culture in higher education, it is still relatively new in the field of postgraduate education (PE for short), particularly when it comes to quality culture from the perspective of learners. This study seeks to identify and analyze the aspects of quality culture (QC for short) that influence the quality of PE in Vietnamese universities in terms of learner satisfaction. Our data from a survey of 256 postgraduate students on 5 factors of QC affecting the quality of PE at several Vietnamese universities was analyzed using SPSS 25.0, and the findings were obtained. The research findings reveal that all parts of quality culture have the same effect on graduate education, with academic variables having the greatest impact on the quality of graduate education from the learner's perspective. The research findings will contribute to the current literature on QC in postgraduate education, as well as provide advice for school leaders when developing a quality culture in PE.